2016
DOI: 10.1016/j.celrep.2016.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial WhiB6 Differentially Regulates ESX-1 and the Dos Regulon to Modulate Granuloma Formation and Virulence in Zebrafish

Abstract: During the course of infection, Mycobacterium tuberculosis (Mtb) is exposed to diverse redox stresses that trigger metabolic and physiological changes. How these stressors are sensed and relayed to the Mtb transcriptional apparatus remains unclear. Here, we provide evidence that WhiB6 differentially regulates the ESX-1 and DosR regulons through its Fe-S cluster. When challenged with NO, WhiB6 continually activates expression of the DosR regulons but regulates ESX-1 expression through initial activation followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 65 publications
5
103
1
Order By: Relevance
“…We found several novel associations most strongly with the AG class of antituberculosis drugs. These include the transcriptional regulator whiB6 that is known to activate expression of the DosR regulon, and controls aerobic and anaerobic metabolism and virulence among other pathways 50 . Previous work has implicated another whiB-like transcriptional regulator, whiB7, in resistance to AGs 51 and whiB6 and the upstream intergenic region were previously associated with resistance in a prior GWAS albeit to non-AG agents.…”
Section: Aminoglycosides (Ag)mentioning
confidence: 99%
“…We found several novel associations most strongly with the AG class of antituberculosis drugs. These include the transcriptional regulator whiB6 that is known to activate expression of the DosR regulon, and controls aerobic and anaerobic metabolism and virulence among other pathways 50 . Previous work has implicated another whiB-like transcriptional regulator, whiB7, in resistance to AGs 51 and whiB6 and the upstream intergenic region were previously associated with resistance in a prior GWAS albeit to non-AG agents.…”
Section: Aminoglycosides (Ag)mentioning
confidence: 99%
“…heat, diamide, NO, cumene peroxide) [155,180]. Recently, Steyn and colleagues showed that WhiB6 from M. marinum (closely related to M. tuberculosis) differentially regulates the DosR dormancy and the ESX-1 virulence factor regulons through its ability to sense NO and oxidative stress via its Fe-S cluster [39]. This led them to propose a model for the function of WhiB6 in which it is upregulated by NO when M. marinum is engulfed by activated macrophages.…”
Section: Wbl Proteins In Mycobacteriamentioning
confidence: 99%
“…ESAT-6 is the virulence factor secreted by ESX-1 secretion system in M. tuberculosis (Solans et al 2014, Chen et al 2016). …”
mentioning
confidence: 99%